Market Barriers and Knowledge Barriers, a Quantitative Study on Entrepreneurial Intention among Female in Yemen - Mohammed Muharram, Shrooq; Alisa Binti Hussain, Ibiwani (International Journal of Psychosocial Rehabilitation, 2020)
The study is to unfold the barriers holding back women in Yemen from setting up a new business by examining the factors of market barriers and knowledge barriers. The data collected of this study through selfadministrated and survey question naire,a total of 120 respondents have participated. The study went through descriptive, frequency and correlation analysis found that there was a significant relation of all the predictive toward entrepreneurial intentions among women in Yemen.